Situational influences on officiating performance: An analysis of foul calls in the Chinese basketball association league (CBA) - Fang Shu; Liqing Zhang; Xiao Xu; Ruohan Xu (PLoS ONE, 2026)
The growing emphasis on situational variables has significantly advanced research in sports performance analysis, yet studies focusing on referees from this perspective remain limited. This study examines how multiple situational variables influence foul calls metrics during the 2022–2023 Chinese Basketball Association League (CBA) season. Drawing on 18,519 foul events from 441 games, with the final analytical sample comprising 18,182 events from 439 games, independent-sample t-tests were used to assess the effects of individual situational variables, and binary logistic regression models were applied to examine their associations. The situational variables analyzed included game system, game type, team quality difference, score differential, and foul differential. Results show that while a clear home advantage emerges in home-and-away games, the overall foul number does not differ across systems. Stronger teams were called more fouls in games with large team quality gap, particularly in the fourth quarter. Leading teams were consistently called for more fouls when score differential widened, and teams with fewer accumulated fouls were more likely to receive subsequent calls, suggesting a potential balancing tendency in officiating. Logistic regression showed that foul calls was significantly associated with score differential, foul differential, and team quality difference, whereas the main effects of game type were limited. Importantly, several variables that were non-significant in single-factor tests emerged as significant in the multivariable models, underscoring the situational nature of officiating. This study enriches understanding of officiating performance within the framework of sports performance analysis. These findings highlight that referees’ decisions are “context-sensitive” rather than random or rigid, meaning they vary across specific competitive situations. Such situational sensitivity may sustain competitive balance and game flow but also introduces risks of officiating bias. Recognizing this dual nature is valuable not only for referee evaluation, but also for leagues governance, as well as for teams seeking to anticipate officiating tendencies during games.